Pengaruh Faktor Perilaku Terhadap Kejadian Hipertensi Di Wilayah Kerja Puskesmas Kanigoro, Kabupaten Blitar - Een Hendarsih; Andi Wahjono Adi; Marintik Illahi; Sintia Wahyu Arifah (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Hypertension is called the silent killer because most people with hypertension do not show symptoms. A decrease in blood pressure in people with hypertension can reduce the risk of cardiovascular disease, while an increase in blood pressure can damage blood vessels that affect organ function and can be life-threatening. 2018 basic health research, the incidence of heart and blood vessel disease is increasing from year to year. The level of awareness and individual behavior to control and manage hypertensionneeds to be increased so that hypertension can be detected and treated immediately so that it does not cause complications and even death. This study aims to analyze the relationship between behavioral factors and the incidence of hypertension in the Kanigoro Health Office, Blitar Regency. This study used the SEM-PLS (Structural Equation Modeling –Partial Least Square) correlation test. Sampling using multistage random sampling method with a sample of 379 people. The analysis uses the SEM –PLS (Structural Equation Modeling –Partial Least Square) program. In the Outer Model, the results of motivation indicators, blood pressure monitoring cards, and the role of health workers have a loading factor value of > 0.7. The results of the structural model from the SEM –PLS analysis show that there is no relationship between behavioral factors and the incidence of hypertension. However, the relationship between behavioral factors has a t-count value above the t-table value (1.96). The results of the structural model from the SEM –PLS analysis show that there is a relationship between behavioral factors. The findings of this study indicate that there is no relationship between behavioral factors and the incidence of hypertension in the Kanigoro Public Health Center, Blitar Regency.